Work-family conflict during the Covid-19 pandemic: teleworking of administrative and technical staff in healthcare. An Italian study: Work-family conflict during the Covid-19 pandemic in healthcare - Ghislieri, Chiara; Molino, Monica; Dolce, Valentina; Sanseverino, Domenico; Presutti, Michele (La Medicina del Lavoro, 2021)
Background: Remote working (more appropriately, mandatory work from home) during the Covid-19 healthcare emergency has increased significantly. Amidst many critical issues, work-family conflict (WFC) remains a central topic, due to the hardships in separating different life domains, the pervasiveness of technology, and decreased opportunities for recovery, all considering new, emerging job demands. Although many studies have involved healthcare workers, less attention has been paid to technical-administrative staff (TA); moreover, previous studies about the impact of remote working on WFC have provided mixed results. Objectives: The study aims at examining the relationships between WFC and cognitive demands, off-work hours technology assisted job demands (off-TAJD) and recovery, in the TA of a hospital in northwest Italy. Methods: A sample of 211 individuals (response rate of 58%), in line with the population, filled in an online self-report questionnaire in the second half of April 2020. Results: Multiple regression analysis showed a positive relationship between WFC and perceived ICT stress, off-TAJD and cognitive demands, and a negative relationship with recovery. Conclusions: The results confirm the role of cognitive demands, technology overload and invasiveness, as potential predictors of WFC. The results also indicate the mitigating role of recovery, even in the face of a prolonged and forced experience of remote work. The study emphasises the need for transparent policies, based on trust, autonomy and right to disconnect, and the centrality of training, especially for supervisors, on topics such as evaluation of results, proper recovery management and correct use of technology.